2013
DOI: 10.1016/j.jsr.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Visual information search in simulated junction negotiation: Gaze transitions of young novice, young experienced and older experienced drivers

Abstract: Older drivers and young novice drivers have problems negotiating road junctions and this is reflected in the accident statistics for these driver populations. Explanations for problems with junction negotiation largely focus on limitations in visual information processing and observation errors associated with age and experience. Investigations of drivers viewing behaviour have used measures of fixation and gaze frequency and duration to highlight drivers information processing and search, capacity and require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…However, transition matrixes have been previously used to study spatial transitions (gaze shifts). For example, Scott et al (2013) studied the width of visual search while subjects were negotiating junctions during driving simulations, and Underwood et al (2005) studied the likelihood of saccades between road zones during hazard detection in a replayed driving situation. These studies both focused on narrow parts of the driving task.…”
Section: Analysis Proceduresmentioning
confidence: 99%
“…However, transition matrixes have been previously used to study spatial transitions (gaze shifts). For example, Scott et al (2013) studied the width of visual search while subjects were negotiating junctions during driving simulations, and Underwood et al (2005) studied the likelihood of saccades between road zones during hazard detection in a replayed driving situation. These studies both focused on narrow parts of the driving task.…”
Section: Analysis Proceduresmentioning
confidence: 99%
“…Klauer (2006) reported that fixating gaze and allocating more attention to a wide range and a distant area are associated with a reduced risk of traffic accidents. Scott et al (2013) also showed remarkable differences in gaze behavior between young novice drivers and young experienced drivers. The experienced drivers showed visual fixations covering a wider range when entering crossroads than those of less experienced drivers.…”
Section: Discussionmentioning
confidence: 93%
“…The location of a point of gaze is typically assumed to index the focus of attention (Duchowski, 2007), when a visual fixation occurs. Therefore the fixation location is often assumed to include the most important task-relevant information, where the performers' attention is allocated (Hamid, Stankiewicz, & Hayhoe, 2010;Scott, Hall, Litchfield, & Westwood, 2013). As such, the quality and quantity of information to be obtained is dependent on when (or how long) and where the gaze is fixated at.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers typically use blinking frequency to evaluate driving fatigue and workloads [7,8,9,10]; gazing and scanning, however, are only considered as effective means to gather traffic information and recognize drivers’ intentions [11,12,13,14,15,16,17]. Common analysis metrics include gaze duration, gaze frequency, saccade duration, saccade frequency, saccade amplitude, and various transition-based parameters between fixation.…”
Section: Introductionmentioning
confidence: 99%